2020
DOI: 10.3390/su12197871
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of the Spatial Extent of Land Subsidence and Aquifer System Drainage Induced by Underground Mining

Abstract: The environmental impact assessment of underground mining usually includes the direct effects of exploitation. These are damage to rock mass and land subsidence. Continuous dewatering of the aquifer system is, however, necessary to carry out underground mining operations. Consequently, the drainage of the aquifer system is observed at a regional scale. The spatial extent of the phenomenon is typically much wider than the direct impact of the exploitation. The research presented was, therefore, aimed at evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…Figure 3. Schematic cross-section of geological strata and aquifer system in the area of interest, modified after [67,146]. The location of the cross-section is depicted in Figure 2.…”
Section: Geologymentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 3. Schematic cross-section of geological strata and aquifer system in the area of interest, modified after [67,146]. The location of the cross-section is depicted in Figure 2.…”
Section: Geologymentioning
confidence: 99%
“…Nonetheless, in many cases, even after the closure of mining operations, mine drainage maintenance is still required for safety reasons [66]. Due to the long-life cycle of underground mines, which can range from a few to several dozen years, the volume of groundwater pumped out of the rock mass is significant and, in many cases, exceeds billions of m 3 [67]. Such a substantial volume of groundwater withdrawn and a long-term process of mining-induced drainage results in a permanent change in the aquifer system's hydraulic conductivity and storage properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of environmental factors in assessing the results of sustainable development of industrial regions, repeatedly noted by the authors [11; 15], is confirmed by an increasing number of research on this topic. The set of environmental indicators depends on the objectives of the research and usually includes data on the amount of emissions and discharges of pollutants, state of soils and surface waters of the region of presence, air pollution, landscape transformation [16][17][18]. Obviously, the emergence and development of industrial clusters is based on the systemic change in the environment.…”
Section: Resultsmentioning
confidence: 99%